Independent Auditors as Fiscal Gatekeepers - Luigi Alberto Franzoni (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1997)
This paper develops a framework for the analysis of gatekeeping in tax enforcement, whereby independent auditors are assigned the duty of certifying taxpayers` reports. The equilibrium of the market for gatekeepers` services is characterized, as well as taxpayers` and auditors` optimal behavior. The paper discusses the optimal structure of the gatekeeping regime and determines the conditions under which it is socially preferable to direct public enforcement.
Keywords: 330